Житлові умови сільського населення в контексті формування соціальної політики - Черніченко, В.В. (Інститут демографії та соціальних досліджень НАН України, 2008)
Статья посвящена исследованию условий проживания населения Украины, в том числе в разрезе разных типов поселений, выявлению причинно-следственных связей между факторами, влияющими на количественные и качественные показатели названных условий. Очерчены направления смягчения следствий негативного влияния разных факторов на условия проживания населения и приоритеты государственной политики в сфере жилищного строительства и на рынке жилья. The article is devoted to research of terms of residence of population of Ukraine, including in the cut of different types of settlements, to the exposure of connections between factors which influence on the quantitative and high-quality indexes of the adopted terms. Outlined directions of softening of consequences of the negative influencing of different factors on the terms of residence populations and priorities of public policy in the field of housing building and at the market of habitation.